Inductive logic programming : 28th International Conference, ILP 2018, Ferrara, Italy, September 2-4, 2018, Proceedings /: 28th International Conference, ILP 2018, Ferrara, Italy, September 2-4, 2018, Proceedings. (2018) - Unknown
No abstract available